2016
DOI: 10.1007/s00158-016-1548-5
|View full text |Cite
|
Sign up to set email alerts
|

Game theory approach to robust topology optimization with uncertain loading

Abstract: The paper concerns robustness with respect to uncertain loading in topology optimization problems. Using a game theoretic framework we formulate problems, or games, defining generalized Nash equilibria. In each game a set of topology design variables aim to find an optimal topology, while a set of load variables aim to find the worst possible load. Several numerical examples with uncertain loading are solved in 2D and 3D. The games are formulated using global stress, mass and compliance as objective functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Attractive features of such algorithms include very simple implementation and parallelization. Decomposition algorithms have previously been used for TO-games, [15][16][17][18][19][20]52,53 although not with the penalty terms used here.…”
Section: Numerical Solution Of Nash Gamesmentioning
confidence: 99%
“…Attractive features of such algorithms include very simple implementation and parallelization. Decomposition algorithms have previously been used for TO-games, [15][16][17][18][19][20]52,53 although not with the penalty terms used here.…”
Section: Numerical Solution Of Nash Gamesmentioning
confidence: 99%
“…A review of the literature reveals many papers dealing with continuum topology optimization formulations to solve stochastic problems and find optimal structures in the presence of uncertainties. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Two main techniques are often used to address design optimization problems under uncertainties: reliability-based design optimization and robust design optimization. 18 In the reliability-based design optimization approach, uncertainties affect only the design constraints, which are written in such a way as to warrant a minimal level of safety for the optimal design.…”
Section: Introductionmentioning
confidence: 99%
“…A careful literature review resulted in 3 recent works providing contributions in this subject. 8,12,17 In Luo et al, 8 an RBTO approach is formulated to solve continuum problems where the objective is the minimum volume subjected to stress constraints under uncertainties in applied loads and material properties; it is demonstrated that the singularity phenomenon is even more challenging in the reliability-based formulation, and a target reliability index relaxation is proposed for helping alleviate this difficulty. In Holmberg et al, 12 a worst-case RTO approach is developed through a game theoretic framework, where applied load with known maximum intensity and unknown direction is modeled as a non-probabilistic uncertainty; it is demonstrated that von Mises stresses do not exceed stress limit, imposed by the designer, considering any loading condition inside predefined ellipsoid in design space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations